2005
DOI: 10.2320/matertrans.46.669
|View full text |Cite
|
Sign up to set email alerts
|

Structure Control of Plasma Sprayed Zircon Coating by Substrate Preheating and Post Heat Treatment

Abstract: Zircon is widely used in industrial field as a refractory material, because of its excellent mechanical and chemical properties at high temperature. Authors have been studied on the effect of the heat treatment on the structure and properties of plasma sprayed zircon coating as a candidate for an environmental barrier coating (EBC). In this study, very dense coating with excellent adhesive strength was successfully obtained by optimizing the spray process. Substrate temperature is one of the dominant factors t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(13 citation statements)
references
References 7 publications
(8 reference statements)
0
13
0
Order By: Relevance
“…Consequently, in the plasma spray deposition of the pseudo‐eutectic alumina–YSZ composite, extensive amorphous‐phase formation is expected. In fact, there are many reports of amorphous phases in alumina–YSZ composite coatings 3–6. Upon exposure to high service temperature, these phases, like other structural features of the coatings, undertake changes that can, in turn, induce important variations in the properties of the deposited materials.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Consequently, in the plasma spray deposition of the pseudo‐eutectic alumina–YSZ composite, extensive amorphous‐phase formation is expected. In fact, there are many reports of amorphous phases in alumina–YSZ composite coatings 3–6. Upon exposure to high service temperature, these phases, like other structural features of the coatings, undertake changes that can, in turn, induce important variations in the properties of the deposited materials.…”
Section: Introductionmentioning
confidence: 99%
“…YSZ,7, 8 alumina,3–10 and their composites (alumina–zirconia)6, 11–13 have been extensively investigated in terms of their crystalline and microstructural changes upon heat treatment, in addition to thermal cycling 7. Sodeoka et al14 studied coatings with 50/50 volume ratio of alumina/3YSZ, and found that after 30 min at 1000 °C, crystallization of the amorphous phase was complete.…”
Section: Introductionmentioning
confidence: 99%
“…The phase diagram of the system ZrO 2 -SiO 2 -Al 2 O 3 (A-B-C) has an immiscibility surface [1,10]. Compound R 2 = ZrO 2 ×SiO 2 decomposes without melt in the binary system ZrO 2 -SiO 2 and the congruently melting compound 3Al 2 O 3 ×2SiO 2 exists in the binary system Al 2 O 3 -SiO 2 [1].…”
Section: Model For Phase Diagram Of System Zro 2 -Sio 2 -Al 2 Omentioning
confidence: 99%
“…However, it is very difficult to fabricate ZrSiO 4 because it has a dissociation line at 1676°C (1949 K), as seen in the phase diagram of Figure ( Butterman and Foster, 1953). Suzuki et al (2005) deposited a dense coating by plasma spray deposition of a ZrO 2 + SiO 2 powder blend and heating the substrates; however, no ZrSiO 4 was present in the coating. The coatings that were subjected to heat treatment at 1673 K for approximately 24 h had a significant amount of ZrSiO 4 , and the coating porosity was high.…”
Section: Future Trendsmentioning
confidence: 99%